Advances in Cell Transplantation Therapy for Limbal Stem Cell Deficiency - Gui, Yujia; He, Yuxi; Wang, Di; Wang, Shurong; Zhang, Yan (Current Stem Cell Research & Therapy, 2024)
Background: Limbal stem cells (LSCs) are essential for maintaining corneal transparency and ocular surface integrity. Many external factors or genetic diseases can lead to corneal limbal stem cell deficiency (LSCD), resulting in the loss of barrier and corneal epithelial cell renewal functions. Stem cell transplantation is one of the primary treatments for LSCD, including limbal transplantation and cultivated limbal epithelial transplantation. In addition, a variety of non-limbal stem cell lines have been experimented with for LSCD treatment. Biological scaffolds are also used to support in vitro stem cell culture and transplantation. Here, we review the mechanisms of corneal maintenance by LSCs, the clinical stage and surgical treatment of LSCD, the source of stem cells, and the biological scaffolds required for in vitro culture. Methods: This study is a narrative retrospective study aimed at collecting available information on various aspects of surgical treatments for LSCD. Relevant literature was searched in a range of online databases, including Web of Science, Scopus, and PubMed from 2005 to March, 2023. Results: A total of 397 relevant articles were found, and 49 articles with strong relevance to the studies in this paper were obtained and analyzed. Moreover, 11 of these articles were on the concept of LSCD and the mechanism of LESCs maintaining the corneal epithelium, 3 articles on the staging and grading of LSCD, 17 articles on cell transplantation methods and donor cell sources, and 18 articles on scaffolds for delivering stem cells. We also summarized the advantages and disadvantages of different cell transplantation methods and the benefits and limitations of scaffolds based on the above literature. Conclusion: The treatment of LSCD is determined by the clinical stage and whether it involves monocular or binocular eyes. Appropriate surgical techniques should be taken for LSCD patients in order to reconstruct the ocular surface, relieve symptoms, and restore visual function. Meanwhile, biological scaffolds assist in the ex vivo culture and implantation of stem cells.
Keywords: Cornea